Pemberdayaan Ekonomi Kreatif: Diversifikasi Produk Ayam Olahan di Tanah Sareal, Bogor - Maya D Dyah Maharani; Tatan Sukwika; Dem Vi Sara; Boedhi Oetojo; Arina Rubyasih (Jurnal Pengabdian Pada Masyarakat, 2021)
EMPOWERING CREATIVE ECONOMY: DIVERSIFICATION OF PROCESSED CHICKEN PRODUCTS IN TANAH SAREAL, BOGOR. The demand for food of animal origin (PAH) is increasing rapidly in Bogor. The demand dominated by broiler products from the Pondokrumput chicken shelter and slaughter facility (TPnA), Tanah Sareal. The TPnA business unit is located in densely populated settlements and sometimes causes social, economic and environmental problems. There is a negative perspective on the neglect of the TPnA business unit in community involvement so that it has negative implications for the existence of the business unit. One of the efforts to reduce its negative impact is to invite the community around TpnA to participate in the processing of TpnA's fresh chicken production into the advanced processed chicken, among others by using the "ungkep" chicken technique. The prospect of the “ungkep” chicken market is promising and can contribute to improving the local community's economy. Chicken "ungkep" has many variations of the preparation to meet the needs of public consumption. Besides, the use of basic spices, spices and proper cooking techniques in chicken produces flavour, without the need for flavourings. This chicken product certainly meets the rules of safe-healthy-whole-halal (ASUH) and is durable. This community service activity was expected to contribute to inspiration, motivation, insight, and creativity. Another contribution is to provide increased knowledge, experience and added value to the business unit for shelters, chicken slaughterhouses (TpnA). Finally, this activity is also useful for local communities who do not yet have a small business base.